Konflik Kepemilikan Properti Akibat Perkawinan Tanpa Akta: Kajian Hukum Keluarga di Era Digital - Devin Jinoto (Jurnal Hukum Lex Generalis, 2025)
Marriage without official registration in Indonesia causes legal conflicts, particularly regarding property ownership and joint assets. The unclear legal status of couples in unregistered marriages complicates the resolution of property disputes in court. This study examines the legal implications of unregistered marriages and the impact of digitalization on resolving property disputes. The results indicate that digitalization can expedite marriage registration and dispute resolution processes, although challenges in regulation and accessibility remain. Legal reform regulating unregistered marriages and the integration of technology are necessary to enhance justice in Indonesia's family law system.